Microstructure, Mechanical Properties, and Fatigue Resistance of an Al-Mg-Sc-Zr Alloy Fabricated by Wire Arc Additive Manufacturing - Lingpeng Zeng; Jiqiang Chen; Tao Li; Zhanglong Tuo; Zuming Zheng; Hanlin Wu (Metals)
Al-Mg alloy wire modified by Sc and Zr additions was used to prepare a high-strength, non-heat-treated Al-Mg alloy component by wire arc additive manufacturing (WAAM) technology in the present work, and the microstructure, mechanical properties, fatigue resistance, as well as their anisotropies of the deposited Al-Mg-Sc-Zr alloy component were studied. The results show that the microstructure of the as-deposited alloy is composed of fine equiaxed grains with an average grain size of around 8 μm, and nanosized Al3(Sc, Zr) particles (~5 nm) are also evident. The tensile properties and fatigue resistance of the deposited alloy showed significant anisotropy, and the performance of the traveling direction is always better than that of the deposition direction. The ultimate strength, yield strength, elongation, and critical fatigue life (cycles) of the as-deposited alloy along the traveling direction (0° direction) are 362 ± 7 MPa, 244 ± 3 MPa and 24.8 ± 0.3%, and 1.72 × 105, respectively. The presence of weak bonding areas and high tensile (positive) residual stress between the deposition layers deteriorate the tensile properties and critical fatigue life of the sample along the deposition direction.